ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TANAMAN KELAPA PADA PERKEBUNAN RAKYAT DI KECAMATAN TAMBANG KABUPATEN KAMPAR - Mirna, Isra; Aulia, Ando Fahda; Aqualdo, Nobel (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the factors that affect the productivity of coconut in smallholder plantations in Subdistrict Tambang Kampar district. The survey was conducted from March - April 2018 to coconut farmers in Tambang Subdistrict, by using purposive sampling technique with sample of 97 respondents. The method used in this research is descriptive analysis and quantitative analysis through simple regression. The result of analysis shows that (1) collectively labor, land area, fertilizer and seedlings have significant effect to coconut productivity. (2) partially, each labor, land area, fertilizer and seedlings give a significant effect to the productivity of coconut in SubDistrict Tambang Kampar district.Keywords : Coconut, Labor, Land Area, fertilizer, seedlings, Tambang Subdistrict